Effect of Heat Treatment on the Microstructure and Mechanical Properties of Al–9Si–0.4Mg–0.1Cu Alloy. Issue 12 (3rd June 2022) - Guo, Binxu; Chang, Liang; Dai, Jiahang; Ding, Yuming; Li, Ri; Ding, Jian; Li, Chong; Tang, Ying; Xia, Xingchuan; Chen, Xueguang; Song, Kaihong; Liu, Yongchang
Abstract : Herein, effect of heat treatment on the microstructure and mechanical properties of a newly developed Al–9Si–0.4Mg–0.1Cu alloy treated by Al–6Sr–7La is investigated, and optimal T6 heat treatment process parameters are determined through optical microscopy (OM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) analysis, and quantitative statistics. The results show that the distribution of α‐Al is more uniform after T6 heat treatment (solution treated at 540 °C for 5 h and aged at 170 °C for 6 h) with eutectic silicon possessing fine grain and high roundness. Meanwhile, Al–6Sr–7La increases peak aging hardness and reduces peak aging time. During the under‐aging process, a large amount of Guinier Preston zone and a small amount of Mg5 Si6 phase precipitate, which have strengthening effect on the alloy. At peak aging state, the coherent precipitated Mg5 Si6 phase in α‐Al leads to the highest microhardness. Continuing to prolong aging time, the coherent relationship between metastable phase Mg5 Si6 and the matrix is weakened, resulting in the decrease in microhardness. In addition, after T6 heat treatment, both tensile strength and elongation of the alloy are significantly improved and the reasons are discussed. Abstract : Herein, effect of heat treatment on the microstructure and mechanical properties of a newly developed Al–9Si–0.4Mg–0.1Cu alloy treated by Al–6Sr–7La is investigated, and optimal T6 heat treatment process parameters (solution treated at 540 °C for 5 h and aged at 170 °C for 6 h) are determined.